10.61533 ANALISIS PENGARUH PERTUMBUHAN UMKM BERBASIS BISNIS DIGITAL DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN PDRB DI KOTA PANGKALPINANG DALAM MENDUKUNG EKONOMI BERKELANJUTAN DAN INKLUSIF - Lydia Laurensia; Ryan Hasianda Tigor; Hendarti Tri Setyo Mulyani (Jurnal Ilmiah Niaga Bisnis Elektronik, 2025)
The background of this paper describes the problem of economic conditions in Pangkalpinang City as reflected in the growth of the Gross Regional Domestic Product (GRDP). The purpose of this final project is to determine the effect of Digital Business-Based MSMEs Growth and The Human Development Index on GRDP Growth in Pangkalpinang City in supporting a sustainable and inclusive economy. Data processing in this research using multiple linear regression analysis, which consists of classical assumption test, hypothesis test, and coefficient of determination test. In this research, there were no problems with the classical assumption test. The regression equation for GRDP growth = -4,112 – 1,252 Digital Business-Based MSMEs Growth + 14,012 Human Development Index. Statistical analysis partially proves the hypothesis (t-test), indicating that Digital Business-Based MSMEs Growth does not effect significant on GRDP Growth. The Human Development Index does not effect significant on GRDP Growth. Simultaneously (F test), proves that Digital Business-Based MSMEs Growth and the Human Development Index together do not have a effect significant on GRDP Growth. The Adjusted R² value obtained is 0,575, proving that Digital Business-Based MSMEs Growth and the Human Development Index have a 57,5% effect on GRDP Growth. Meanwhile, the remaining 42,5% is influenced by other variables not examined in this research.